2013
DOI: 10.1105/tpc.113.117127
|View full text |Cite
|
Sign up to set email alerts
|

The R2R3-MYB Transcription Factors MYB14 and MYB15 Regulate Stilbene Biosynthesis in Vitis vinifera

Abstract: Plant stilbenes are phytoalexins that accumulate in a small number of plant species, including grapevine (Vitis vinifera), in response to biotic and abiotic stresses and have been implicated in many beneficial effects on human health. In particular, resveratrol, the basic unit of all other complex stilbenes, has received widespread attention because of its cardio-protective, anticarcinogenic, and antioxidant properties. Although stilbene synthases (STSs), the key enzymes responsible for resveratrol biosynthesi… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

13
256
1

Year Published

2015
2015
2022
2022

Publication Types

Select...
3
3
1

Relationship

0
7

Authors

Journals

citations
Cited by 269 publications
(276 citation statements)
references
References 104 publications
13
256
1
Order By: Relevance
“…Fang et al (2014) showed that the variation in expression of MYB14 correlated with the variation in resveratrol content in two grapevine cultivars (Vitis monticola 9 Vitis riparia with a high resveratrol content and V. vinifera with a low resveratrol content). In addition, Fang et al (2014) confirmed the data by Höll et al (2013) that the expression patterns of MYB14 and STS were almost identical under UV-C treatment. Using a one-hybrid yeast assay, they also found that MYB14 directly interacts with the STS promoter (Box-L5 motif) in vitro.…”
Section: Transcriptional Regulation Of Stilbene Biosynthesis In Plantssupporting
confidence: 77%
See 3 more Smart Citations
“…Fang et al (2014) showed that the variation in expression of MYB14 correlated with the variation in resveratrol content in two grapevine cultivars (Vitis monticola 9 Vitis riparia with a high resveratrol content and V. vinifera with a low resveratrol content). In addition, Fang et al (2014) confirmed the data by Höll et al (2013) that the expression patterns of MYB14 and STS were almost identical under UV-C treatment. Using a one-hybrid yeast assay, they also found that MYB14 directly interacts with the STS promoter (Box-L5 motif) in vitro.…”
Section: Transcriptional Regulation Of Stilbene Biosynthesis In Plantssupporting
confidence: 77%
“…Cell suspensions of V. vinifera and tobacco leaves transiently expressing STS luciferase reporter constructs showed considerable induction of the STS29 and STS41 promoter activities when co-transformed with MYB14 and MYB15. To confirm the involvement of these TFs in the regulation of stilbene biosynthesis in planta, Höll et al (2013) obtained grapevine hairy roots overexpressing MYB15 and revealed that an increased accumulation of t-piceid was coupled to the up-regulation of STS29 and STS41 transcription levels in the hairy root line. Taken together, the results by Höll et al (2013) indicated that MYB14 and MYB15 TFs are involved in the induction of STS29 and STS41 transcription in V. vinifera.…”
Section: Transcriptional Regulation Of Stilbene Biosynthesis In Plantsmentioning
confidence: 99%
See 2 more Smart Citations
“…Stilbenoids (resveratrol in particular) are powerful defence antioxidant molecules found in several species and their accumulation is particularly high in grapevine (Vannozzi et al, 2012;Höll et al, 2013;Stuart and Robb, 2013). Furthermore, it has been suggested that flavonoids, whose biosynthetic genes are induced only in M4 leaves under WS ( Figure 3B), act as antioxidants in plant response to oxidative stresses (Brunetti et al, 2013).…”
Section: Resultsmentioning
confidence: 99%